Manajemen Pembelajaran untuk Meningkatkan Prestasi Siwa - Putri, Nigel Apriliyani; Nurfuadi, Nurfuadi (DIDAKTIKA, 2023)
Learning management is a process carried out by the teacher in managing and directing learning activities in the classroom. Good learning management can improve student achievement, because it is able to have a positive influence on motivation, creativity, and students' understanding of learning material. In learning management, there are several things that need to be considered by the teacher, including planning, implementing, evaluating, and developing learning. In planning lessons, teachers must set clear learning objectives, determine effective learning methods, and choose relevant learning materials. While in the implementation of learning, teachers must be able to facilitate learning well, manage learning time, and motivate students to be active in the learning process. Furthermore, in learning evaluation, teachers need to periodically evaluate student learning outcomes, provide constructive feedback, and make improvements to learning methods and materials if necessary. In the end, the development of learning is an important matter in learning management. Teachers need to keep abreast of technological and pedagogical developments, and always develop their own abilities in leading and managing learning. By implementing good learning management, it is hoped that it can improve student achievement, as well as create a conducive and enjoyable learning environment.